Citra Perempuan Sunda dalam Kumpulan Cerita Pendek Sisa Bulan Karya Imas Rohilah - Ayesha Nurpujia B; Dedi Koswana; Chye Retty Isnendes (PANALUNGTIK, 2024)
The purpose of this research is to describe: 1) the story structure that appears in the short story collection Bulan Sesa; and 2) the image of Sundanese women that appears in the short story collection Bulan Sesa. The method used is descriptive-analytical, which aims to describe the structure and image that appears in the short stories. The technique used is literature study, the results are: 1) the theme that appears in the short stories is about the fate of oppressed women, because they face simple but complex problems. The storyline that appears in the short story collection Bulan Sesa is between the beginning, middle, and end, each event is continuous. In these three parts, there are stages of introducing the situation, the emergence of problems, conflicts, climax, and even the resolution stages. The settings in this collection of stories include the setting of the place where the events occur, the setting of the place as a description, the setting of the time when the events occur, the setting of the time that shows the description, the setting of the time that shows the period, and the social setting. The characters that appear are mostly female characters. The characteristics depicted are women who are devout, both to their worship and to their husbands. 2) The images of women depicted in Imas Rohilah's stories mostly depict marginalized women, who have the strength to fight against the majority. It is recommended that there be more feminist research, especially on the images that appear in the novels. Meanwhile, the analysis needs to consider the issue of time. For example, studying the feminism of Sundanese novels before the war, after the war, the New Order, or literary objects used and written by the current generation.